Comparison Of Authority Of The Conditional Court In India And Thailand In Judicial Review - Indah Satria (Bandar Lampung University, 2015)
All countries which transformed into democracies at the end of the 20th century established constitutional courts. Thailand and Indonesia established constitutional courts following their transformation into new democracies. For Thailand and Indonesia, the presence of the Court is already long overdue. The main target of the establishment of this institution cannot be separated from the ideals of the legal state. As is known, generally countries that have looked at the written law constitutional text as a collection of the highest legal doctrines. This raises the legal consequences if a product is contrary to the constitution, the supreme doctrine requires cancellation action on the legal product. As for the problem in this paper is how it compares to the authority of the Constitutional Court in Indonesia and Thailand in judicial review. The method used in this research is normative juridical. Constitutional Court of Thailand can review and decide upon the constitutionality draft of laws or draft organic law approved by the National Assembly. However, based on the provisions that have been enacted, the constitutional court of Thailand carry out reviewing of the object of legal norms that have been established or disconnected constitutionality after the Bill is enacted. While in Indonesia, judicial review benchmarks performed with the Constitution. In contrast to the Constitutional Court of Thailand, Constitutional Court of Indonesia cannot examine the Draft of Laws. However, the existence of the Constitutional Court in Indonesia and Thailand has actually functioned optimally. It is effort to maintain the basic rights of the people. Through the way people's preferences in questioning the actions that are considered controversial state apparatus can be organized fairly and accurately. It can be said as the media is able to bridge the community in finding constitutional justice.